An Analysis of Financial Report on Profitability of Financial Institutions In Indonesia Stock Exchange - Slamet Santosa (International Journal of Seocology, 2019)
This research was conducted to determine the effect of liquidity, NPL, and capital structure on the profitability of banking financial institutions on the Indonesia Stock Exchange partially and simultaneously. The research method uses a quantitative approach. Data analysis techniques used in this study were multiple regression analysis techniques. Testing research data using the classic assumption test, normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The results showed that 1) Liquidity variables have an influence on bank profitability. This causes the customer to trust the bank in providing credit services due to the bank's ability to refinance its obligations to customers who hold their funds using current assets that are running well. 2) The NPL variable has no influence on bank profitability. This causes the amount of problem loans to be greater, causing problems, namely losses caused by the rate of return on bad loans. 3) Variable capital structure has no influence on bank profitability. This is because bank capital is not channeled to the public, thus making the capital unproductive and not producing profits for the company. 4) Simultaneously changes in liquidity, NPL and capital structure variables together have a significant effect on the profitability of banks on the Indonesia Stock Exchange.